Voluntary exercise modulates pathways associated with amelioration of retinal degenerative diseases - Chu-Tan, Joshua A.; Cioanca, Adrian V.; Wooff, Yvette; Kirkby, Max; Ellis, Marissa; Gulati, Pranay; Karl, Tim; Boatright, Jeffrey H.; Bales, Katie; Nickerson, John; Natoli, Riccardo (Frontiers in Physiology, 2023)
Background: Exercise has been shown to promote a healthier and longer life and linked to a reduced risk of developing neurodegenerative diseases including retinal degenerations. However, the molecular pathways underpinning exercise-induced cellular protection are not well understood. In this work we aim to profile the molecular changes underlying exercise-induced retinal protection and investigate how exercise-induced inflammatory pathway modulation may slow the progression of retinal degenerations. Methods: Female C57Bl/6J mice at 6 weeks old were given free access to open voluntary running wheels for a period of 28 days and then subjected to 5 days of photo-oxidative damage (PD)-induced retinal degeneration. Following, retinal function (electroretinography; ERG), morphology (optical coherence tomography; OCT) and measures of cell death (TUNEL) and inflammation (IBA1) were analysed and compared to sedentary controls. To decipher global gene expression changes as a result of voluntary exercise, RNA sequencing and pathway and modular gene co-expression analyses were performed on retinal lysates of exercised and sedentary mice that were subjected to PD, as well as healthy dim-reared controls. Results: Following 5 days of PD, exercised mice had significantly preserved retinal function, integrity and reduced levels of retinal cell death and inflammation, compared to sedentary controls. In response to voluntary exercise, inflammatory and extracellular matrix integrity pathways were significantly modulated, with the gene expression profile of exercised mice more closely trending towards that of a healthy dim-reared retina. Conclusions: We suggest that voluntary exercise may mediate retinal protection by influencing key pathways involved in regulating retinal health and shifting the transcriptomic profile to a healthy phenotype.